Clamshell as biosorbent – fixed bed adsorption evaluation of calcined clamshells as biosorbent for the column adsorption of methyl orange dye from liquid phase - Abdullah, Luqman Chuah; Mohd Suhaimy, Suhanna Natalya; Zhi, Yang Heng; Adeyi, Abel Adekanmi; Choon, Yoong Cheok (Editorial Board of Journal of Harbin Engineering, 2024)
The wastewater discharged from textile, dyeing, leather and paper industries contains hazardous dye which is the main source of water pollution, leading to water quality degradation. In this study, the clamshell or known as Orbicularia Orbiculata by its scientific name was used as low-cost adsorbent to remove methyl orange (MO) from aqueous solution. The clamshell was activated through thermal treatment to produce the calcined clamshells biosorbent for this adsorption study. The calcined clamshell was characterized by using scanning electron microscope (SEM) and Fourier Transform Infrared (FTIR) spectroscopy. The effect of bed height, initial dye concentration and contact time were investigated in the column adsorptive study. As a result, the optimum adsorption condition for methyl orange achieved the maximum removal percentage of 96.65% at the bed height of 10 cm, initial dye concentration of 10 mg/L and contact time of 10 minutes. The removal percentage increased with the increasing of bed height; however, the opposite trend was observed for initial dye concentration and contact time. The kinetic studies were evaluated by employing the pseudo-first-order model, pseudo-second order, Thomas model and Yoon-Nelson model. Pseudo-second-order model and Yoon-Nelson model were found to be well-fitted the dynamic behavior of adsorption of methyl orange onto the calcined clamshells. The results obtained from this study suggested that clamshells can be an effective adsorbent in the treatment of dye-bearing wastewater.